Peripheralization, Ejidos and Agricultural Livelihoods in Intermediate Mexican Cities: The Importance of Collective Agency to Reduce Vulnerabilities - Méndez-Lemus, Yadira; Vieyra, Antonio; Poncela, Lorena; de la Tejera, Beatriz; Ruiz-López, Cinthia (Frontiers in Sustainable Cities, 2022)
This paper focuses on the interactions between peripheralization, vulnerabilities of agricultural livelihoods, and local collective agency in the creation of new capabilities in intermediate cities. It discusses the theoretical implications of a study conducted in the municipality of Tarímbaro, part of the intermediate city of Morelia, Mexico; it expands on results already published in preliminary form. The unit of analysis was the ejido, since this type of social land tenure, granted to landless peasants in 1917 after the Mexican Revolution, is one of the most important forms of social organization in rural Mexico. About one-half of the Mexican territory comprises >30,000 community-based land tenures (mainly ejidos), and a high proportion of the land now occupied by urban centres was ejido land. This paper uses the example of fifteen ejidos, notably affected by the expansion of Morelia city, to illustrate how local (rural) organizations can foster collective agency to reduce differential vulnerabilities in peri-urban agricultural livelihoods in intermediate cities. In 2015, a semi-structured interview was undertaken with the president of each ejido, followed by a survey of 61 individuals from eleven of the fifteen ejidos. The peripheralization of Morelia has produced inequalities in the adjacent municipality of Tarímbaro. Differential vulnerabilities in peri-urban agricultural livelihoods were found in the participant ejidos. Not all the ejidos have been successful in addressing vulnerabilities associated with urbanization of agricultural land, but those who have achieved some success have certain characteristics that reinforce common values and motivations to establish common goals to sustain local livelihoods. This paper highlights the importance of functional (rural) organizations in regulating access to, and distribution of, resources in the peripheries of intermediate cities.